Non-binary gender dan pendidikan fitrah seksualitas anak - Fairuzillah, Muhammad Naufal; Mumtazi, Fahman; Sutoyo, Yongki (Ta’dibuna: Jurnal Pendidikan Islam, 2023)
One of the gender identities that is developing in society and trying to be recognized for its existence is non-binary gender. Non-binary gender is a term to describe someone who claims he does not refer to the gender of male or female. This paper attempts to describe the essence of non-binary gender discourse, criticism and review of Islamic perspectives, as well as fitrah education on sexuality as an effort to fortify a generation of children against the emergence of this gender variation which is part of LGBTQ+. This research is a literature review based on various relevant literature. The difference between male and female with all their characteristics, looks and roles is a universal principle in the social life. The human tendency to behave according to his sex is natural. In this liberalism era, it is imperative for parents and educators to care for and develop their children’s nature of sexuality as early as possible. Abstrak Salah satu identitas gender yang berkembang di masyarakat dan berusaha diakui keberadaannya adalah gender non-biner (non-binary gender). Gender non-biner adalah istilah untuk menggambarkan seseorang yang mengakui dirinya tidak mengacu pada gender perempuan atau laki-laki. Tulisan ini berupaya menjabarkan hakikat adanya diskursus gender non-biner, kritik dan tinjauan perspektif Islam, serta pendidikan fitrah seksualitas sebagai upaya membendung generasi anak-anak dari munculnya variasi gender ini yang merupakan bagian dari LGBTQ+. Penelitian ini merupakan kajian pustaka dengan merujuk pada berbagai literatur yang relevan. Perbedaan antara laki-laki dan perempuan dengan segala watak, rupa dan perannya masing-masing adalah prinsip universal dalam kehidupan sosial masyarakat. Kecenderungan manusia untuk bersikap sesuai dengan jenis kelaminnya adalah suatu fitrah yang telah tertanam sejak lahir. Di zaman yang marak akan paham liberalisme ini, suatu keharusan bagi orang tua dan pendidik untuk merawat dan mengembangkan fitrah seksualitas anaknya sedini mungkin.